Garpaz enterprises Inc. Growth Plan: Before and after implementation - Salvosa, John Andrew B. (Animo Repository, 2016)
This paper is a continuation of the Garpaz Enterprises, Inc. growth plan which provides a before-and-after analysis of the implementation of the proposed short-term tenant retention and market penetration strategies and to lay the groundwork for the long-term assets improvement strategy. The proposed short-term strategies were assessed during a 12-month implementation period using actual experience to recognize the most relevant internal and external factors affecting Garpaz Enterprises and to identify the most practical solutions put into effect during implementation. The 7-S framework model was used to determine the organizational effectiveness of the activities that were carried out during strategy implementation. A comparative financial and occupancy rate analysis was conducted to measure the financial and marketing performance of the company against the previous year and the projections from the growth plan proposal. Over the course of one year, external opportunities from regional economic growth and threats from competition have not declined. The Information Technology (I.T.) sector on the other hand, was deemed less relevant to Garpaz Enterprises current commercial buildings due to the lack of infrastructure to support that industry. As for the internal factors, the strong points of Garpaz Enterprises remain to be the strategic location of the buildings, low-overhead costs, profitability and financial stability. The implementation of the market penetration strategy has converted its weakness of having no marketing to the strength of pro-active marketing. Fixed assets improvement is an ongoing effort to address the weaknesses in the aging buildings and idle fixed assets of the company. An overview of the actual market penetration and tenant retention activities are outlined below: Tenant retention strategy implementation primary activities: Administration and building operational systems formalization Improvement of property management and tenant services Replacement of undesirable employees Employees are now issued with guidelines and are supervised Building repairs and maintenance (also part of fixed assets improvement) Market penetration strategy implementation primary activities: Pricing adjustments Handling of prospective tenant inquiries Installation of Commercial Spaces for Rent signage Print ads The tenant retention activities have centered around improving the building management operational systems which have led to the reduction in complaints and increased tenant satisfaction. The market penetration strategy implementation has resulted in the increase in frequency of prospective tenant inquiries. After strategy implementation, occupancy has increased slightly by 5% and net profits for the company increased significantly due to the combined higher revenues from new tenants and rental increases for renewing tenants, and the lower operational expenses for the year. Overall, the strategy implementation has had a positive effect on the business and it is recommended that the management of Garpaz Enterprises continue with the long-term assets improvement strategy implementation to maximize the revenue generating opportunities of its fixed assets.